Konsep Berdakwah pada Remaja di era Gadget society - Risky, Abu (ABHATS: Jurnal Islam Ulil Albab, 2025)
This study discusses the concept of da’wah (Islamic preaching) directed toward adolescents in the era of the gadget society, which is characterized by a high dependence on digital technology and social media. Adolescents represent an age group that is highly vulnerable to external influences, both positive and negative, making the right approach to da’wah particularly important. This research employs a literature review method to identify relevant da’wah strategies within the digital context. The findings indicate that social media plays a strategic role in disseminating Islamic values to adolescents through various forms of content such as writings, videos, podcasts, and direct interaction. Digital da’wah enables two-way communication, facilitates the clarification of teachings, and fosters emotional closeness between da’i (preacher) and mad’u (audience). Furthermore, this study emphasizes the need for collaborative da’wah, responsive monitoring of audiences, and the strengthening of religious education through creative and educational digital media. The novelty of this research lies in the integration of multimodal approaches, case studies of youth communities, the application of social theory, and the direct involvement of adolescents in determining the effectiveness of da’wah. Thus, da’wah in the digital era is not only a medium for delivering information but also an essential instrument in shaping the morals, identity, and spiritual awareness of adolescents. [Penelitian ini membahas konsep dakwah kepada remaja di era gadget society yang ditandai dengan ketergantungan tinggi pada teknologi digital dan media sosial. Remaja merupakan kelompok usia yang rentan terhadap pengaruh eksternal, baik positif maupun negatif, sehingga pendekatan dakwah yang tepat menjadi sangat penting. Penelitian ini menggunakan metode literature review untuk mengidentifikasi strategi dakwah yang relevan dalam konteks digital. Hasil kajian menunjukkan bahwa media sosial memiliki peran strategis dalam penyebaran nilai-nilai islam kepada remaja melalui berbagai bentuk konten, seperti tulisan, video, podcast, dan interaksi langsung. Dakwah digital memungkinkan komunikasi dua arah, memfasilitasi klarifikasi ajaran, serta membangun kedekatan emosional antara da’i dan mad’u. Selain itu, penelitian menekankan perlunya dakwah kolaboratif, pemantauan responsif terhadap audiens, serta penguatan pendidikan agama berbasis media digital yang kreatif dan edukatif. Kebaruan penelitian ini terletak pada integrasi pendekatan multimodal, studi kasus komunitas remaja, penerapan teori sosial, serta keterlibatan langsung remaja dalam menentukan efektivitas dakwah. Dengan demikian, dakwah di era digital bukan hanya sarana penyampaian informasi, tetapi juga instrumen penting dalam pembentukan akhlak, identitas, dan kesadaran spiritual remaja.]